Consumer acceptability of beef from two sexes supplemented with essential oil mix - Guerrero, A.; Rivaroli, D. C. [UNESP]; Sanudo, C.; Campo, M. M.; Valero, M. V.; Jorge, A. M. [UNESP]; Prado, I. N. (Csiro Publishing, 2018)
Essential oils are natural extracts from plants which can be included in cattle diets as an alternative to additives, such as ionophores, to improve the shelf life of meat. The aim of this study was to evaluate the sensory acceptability of meat from 57 crossbred (1/2 Angus-1/2 Nellore) animals of different sexes [heifers n = 30, and young bulls n = 27], finished in feedlot with isoenergetic and isonitrogenous diets, which differed in the level of supplementation (0.0, 3.5 or 7.0 g/animal/ day) with a commercial mix of essential oils (Mixoil (R)) from seven plants: oregano, garlic, lemon, rosemary, thyme, eucalyptus and sweet orange. The Longissimus thoracis muscle, aged for 24 h, was evaluated by 120 consumers who scored tenderness acceptability, flavour acceptability and overall acceptability using a hedonic 9-point scale. The inclusion of essential oils affected tenderness acceptability and flavour acceptability (P <= 0.01), with a tendency (P < 0.10) for overall acceptability. Meat from heifers was more appreciated by consumers than that from young bulls in all attributes (P <= 0.001), however, different groups of consumers had different preferences. The inclusion of a mix of essential oils in beef diets was well accepted by consumers, and could improve the acceptability of meat from young bulls, when is added at a concentration of 3.5 g/animal/day during the last 4 months of fattening.
Keywords: beef acceptability; crossbred; heifers; natural additives; young bulls